In Search for New Rationality - Šliogeris, Arvydas (Problemos, 1975)
In the article some aspects of the social philosophical doctrine of H. Marcuse, a famous western sociologist and critic of culture, are analysed. The author investigates the Marcusian interpretation of interdependence between social and cognitive structures, i.e., interconditionality of the technological universe of modern industrial society and the scientific-philosophical acquisition of the world. In the first part of the article the author criticises from the Marxist point of view the Marcusian analysis of the socio-anthropological structure of modern capitalist society and the alternative variants of its revolutionary reform; he criticises the Marcusian understanding of science and scientific cognition of the world, “logic of domination”, immanently leading to the creation of the social repressive mechanism of modern capitalist society.